Designing Authentic Tasks for Communicative Competence - Kalayo Hasibuan; Dilla Apriani; Najla Nuri Adillah; Siti Nurbaithi (Institut Teknologi Pendidikan Indonesia, 2026)
Communicative competence is one of the essential goals in English language teaching because students are expected not only to understand grammar but also to use language appropriately in real communication. However, many classroom activities still focus on memorization and mechanical exercises, which students’ opportunities to practice meaningful interaction. This paper discusses the importance of designing authentic tasks to develop students’ communicative competence in English learning. The study employed a qualitative descriptive method through library research by analyzing books, journal articles, and previous studies related to communicative language teaching and authentic assessment. The findings reveal that authentic tasks encourage students to use language in realistic contexts, improve interaction skills, increase motivation, and develop critical thinking. Tasks such as role plays, interviews, problem-solving activities, presentations, and project-based learning provide opportunities for students to communicate naturally. Furthermore, authentic tasks help teachers create student-centered classrooms where learners actively participate in communication. Therefore, integrating authentic tasks into English language teaching can effectively support the development of communicative competence among learners.